Reshaping mental models – enabling innovation through service design - Vink, Josina; Edvardsson, Bo; Wetter-Edman, Katarina; Tronvoll, Bård (International journal of service industry management, 2019)
Purpose The purpose of this paper is to analyze how service design practices reshape mental models to enable innovation. Mental models are actors’ assumptions and beliefs that guide their behavior and interpretation of their environment. Design/methodology/approach This paper offers a conceptual framework for innovation in service ecosystems through service design that connects the macro view of innovation as changing institutional arrangements with the micro view of innovation as reshaping actors’ mental models. Furthermore, through an 18-month ethnographic study of service design practices in the context of healthcare, how service design practices reshape mental models to enable innovation is investigated. Findings This research highlights that service design reshapes mental models through the practices of sensing surprise, perceiving multiples and embodying alternatives. This paper delineates the enabling conditions for these practices to occur, such as coaching, diverse participation and supportive physical materials. Research limitations/implications This study brings forward the underappreciated role of actors’ mental models in innovation. It highlights that innovation in service ecosystems is not simply about actors making changes to their external context but also actors shifting their own assumptions and beliefs. Practical implications This paper offers insights for service managers and service designers interested in supporting innovation on how to catalyze shifts in actors’ mental models by creating the conditions for specific service design practices. Originality/value This paper is the first to shed light on the central role of actors’ mental models in innovation and identify the service design practices that reshape mental models.